SINERGITAS PEMBANGUNAN KEBUDAYAAN MELAYU (STUDI DUNIA MELAYU DUNIA ISLAM (DMDI) PROVINSI RIAU - Ermanita "; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Riau is located on the world's highways very precise culture serve as a meeting point of creativity and the closest and also central to the neighboring countries. As the Riau provincial government efforts in building and supporting the development of the Malay culture itself has been demonstrated by the Vision Riau (Riau Master Plan 2020) which set out in the Riau Provincial regulations No. 36 of 2001 to make the Riau Malay cultural center. The purpose of research is to determine how to exercise the synergy of actors involved in the development of Malay culture and who the actors involved in the synergy. This type of research is descriptive qualitative research method. The location study was conducted in the city of Pekanbaru. Data collected by observation, interview and document study.Results from these studies showed that a synergy between actors or stalkholder involved in the problems of Malay culture is still not established effectively. Synergy that occurs between DMDI foundation itself has not been intensely intertwined with the agency as a benchmark for success in 2020 the Office of Riau Province culture. However, this will be a special concern of the Department of culture to make DMDI as a priority on its development foundation based Riau Province Malay and Islamic Culture. As has become the target of Riau Master Plan 2020.Key words:Actor, Master Plan, Culture, Development, Synergy